Association between built environment characteristics and metro usage at station level with a big data approach. (July 2022) - Chen, Long; Lu, Yi; Liu, Yanfang; Yang, Linchuan; Peng, Mingjun; Liu, Yaolin
Highlights: A rule-based model was used to identify commuting trips using metro service with smart card data (SCD). Metro usage for commuting mode share and ridership were measured at station level. Metro commuting mode share is negatively associated with population density, while street intersection shows a positive relationship. Office-oriented urban function and street intersection density is positively correlated with metro ridership. Land use diversity was not found significant association with metro usage in Wuhan in 2015. Abstract: Transit-oriented development (TOD) planning strategy has been widely implemented worldwide to formulate dense, mixed-use built environment in the past three decades. The primary goal of TOD is to promote public transit usage including both transit mode share and ridership. Research supports that built environment characteristics around metro stations affect residents' travel behaviors and metro usage. However, the evidence remains inconsistent in different urban contexts. Furthermore, research focusing on mode share such as commuting trips at station level is still scarce. In this study, a rule-based model was used to identify commuting trips using metro service with smart card data (SCD), covering more than 90 percent of all metro passengers in Wuhan, China. Built environment characteristics around metro stations were measured with a 3Ds framework (density, diversity, and design). Results suggest that population density is negatively associated with metro commuting mode share, while street intersection shows a positive relationship. Office-oriented urban function and street intersection are positively correlated with metro ridership. Hence, exploring the fine-grained relationship of metro usage and built environment factors around transit stations in different urban and social contexts warrants further research attention.